A Review on the Pathogenesis and Management of Vatavyadhi with Focus on the scope for Rasayana therapy - Priyalakshmi , S; Resmi , B G; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2022)
Rasayana means a path or system to acquire Rasa or adequate nutrition for the body. It is a special therapy or modality which provides proper nourishment to every cell or tissue of the body. It also normalizes cell functions and preserves health at the molecular level. Ayurveda classifies Rasayana into various types that can be used according to the context. Vata, one of the Tridosha, is the prime driving force behind all body activities. When Vata becomes imbalanced, it disrupts all of the events in the body, causing a variety of damage and diseases. Vata vyadhi refers to a group of diseases caused by vitiated Vata. Though it should be predominant in old age, because of today’s fast-paced and hectic lifestyle, stress etc its occurrence seems to increase in young adults too. Rasayana is a way to achieve homeostasis and thus retarding the process of the aging phenomenon and preventing diseases. Rasayana chikitsa or Jara Chikitsa which has been given a distinguished place in Ayurvedic Samhitas due to its importance in rejuvenating all the cells of the body, holds to serve positive results, particularly in the management of Vatavyadhi